He (和), A Peace-oriented Philosophy - Anwen Zheng (Wolters Kluwer Health/LWW, 2020)
An account of historical background, definition, and application of he（和）in traditional Chinese medicine is given in this article. It is mutual respect and tolerance that lay a solid foundation for he（和）, which has deeply shaped the Chinese culture.